Reconstruction of Pancasila and Citizenship Learning Thinking to Improve Soft Skills of Polytechnic Students - Ananto, Purnomo; Dwilanisusantya, Carissa (Indonesian Journal of Multidisciplinary Science, 2023)
Efforts to reconstruct the learning thinking of Civic Pancasila Education to develop a Life Skills Education Approach. This is based on researchers' concerns about the gap between what actually exists, with the existing conceptual framework (Das Sein and Das Solen), in the education system in Indonesia, especially Civic Education in the development of Polytechnic students. The researchers focus on the application of education theory as a tool of social integration that acts as an agent of value cultivation, Education is strength, Education is an investment for human resource development  or Human Capital theory, and social action theory or Action Theory with the AGIL scheme (Adaptation, Goal Attaintment, Integration, and Latency). This research used a qualitative approach to find and reconstruct the thinking (Constructivism) of Pancasila and Civic Education to develop a Life Skills Education Approach, with a phenomenological approach. Researchers rely on as many of the views of the participants studied according to the research theme in depth as possible to explore and find the right reconstruction of thinking. The conclusions of this study are: (1) The transmission of civic values or social systems in educational institutions is carried out by civic education; (2) Civic education must be shape the character and life skills needed in human resource development; (3) Life  skills education (soft skills) in civic education which is the basic foundation for the formation of an intelligent and good national character is, a very important part used as a learning approach to Pancasila and citizenship education at Polytechnics.